An İnvestigation on its microstructure of the concrete containing waste vehicle tire - Emiroğlu, Emir; Yıldız, Servet (My University, 2008)
The scanning electron microscope(SEM) is one of the most important instruments available for the examination and analysis of microstructural charecteristics of materials. The primary reason for the SEM's advantage is the high resolution that can be abtained when they are examined.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: İnvestigation; concrete containing